Enhancing academic literacy among tertiary learners : a Malaysian experience - Radha M. K. Nambiar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
A vast majority of Malaysian tertiary learners find reading, interpreting and critically evaluating an academic text, the cornerstone of much tertiary study, simply overwhelming especially when they have to rise to the challenge of presenting their understanding in a written or spoken form. The question that needs to be asked and answered now is what we, as educators, can do to help our learners cope with this demanding task ahead of them. An understanding of what difficulties learners face with academic literacy of this kind required in a tertiary institution will help us identify best practices to adopt to enhance academic literacy levels among these learners. This paper draws from a case study that set out to identify strategies learners employ to read an academic text for the purpose of presenting an oral summary of the text. Data was collected using think-aloud protocols, semi-structured interviews and a background questionnaire. The protocols were transcribed and analyzed for strategy use while information from the interviews and questionnaire help validate the strategies learners employed. The findings reveal that learners are not analytical or critical when they read and tend to use surface level processing of text all of which suggest they are not read to cope with academic literacy. The paper ends with suggestions on measures to help prepare learners for academic literacy